Beyond 'platformisation': Designing a mixed-methods approach to inspect (digital) working conditions through organisational systems. (14th May 2022) - Cornet, Maxime; Le Ludec, Clément; Wahal, Elinor; Joulin, Mandie
Abstract : The transformations brought by the digitisation of work and the emergence of platform labour have deep implications for working conditions. However, researchers face difficulties studying platformised work. Workers' invisibilisation and the lack of physical co-presence renders field access difficult. How can the variety of platforms, their organisational systems and the working conditions they offer be accounted for? In this article, we propose a mixed-methods methodology to study platforms in all their diversity by articulating the macro level – the market structure revealed through a multiple correspondence analysis – and the micro level – detailed studies of targeted platforms carried out using desk research. We apply this method in two projects, and, in each case, a typology emerges that supports the need for a diversification of the concept of 'platform labour' when related to working conditions.